The role of artificial intelligence and image processing in the diagnosis, treatment, and prognosis of liver cancer: a narrative-review - Platon Dimopoulos; Admir Mulita; Andreas Antzoulas; Sylvain Bodard; Vasileios Leivaditis; Ioanna Akrida; Nikolaos Benetatos; Konstantinos Katsanos; Christos-Nikolaos Anagnostopoulos; Francesk Mulita (Gastroenterology Review)
Artificial intelligence (AI) and image processing are revolutionising the diagnosis and management of liver cancer. Recent advancements showcase AI’s ability to analyse medical imaging data, like computed tomography scans and magnetic resonance imaging, accurately detecting and classifying liver cancer lesions for early intervention. Predictive models aid prognosis estimation and recurrence pattern identification, facilitating personalised treatment planning. Image processing techniques enhance data analysis by precise segmentation of liver structures, fusion of information from multiple modalities, and feature extraction for informed decision-making. Despite progress, challenges persist, including the need for standardised datasets and regulatory considerations.